A contribution to the "Christian interpretationa of the ethics of straighforward thinking" - Dura, Adam (Folia Philosophica, 2000)
Józef Bańka, the inventor of the ethics of straightforward thinking, envisages a possibility of its "Christian form”. The author, inspired by the above suggestion, makes a successful attempt to overcome the antinomy between the category of „now” as it appears in the straightforward thinking, and the Christian notion of "eternity”. This is achieved on the basis of Wilfrid Stinissen’s concept of "Christian time”. Stinissen. a friend of Claudel, is a Belgian philosopher and a member of one of religious orders.